2010
DOI: 10.1007/s00277-010-1135-6
|View full text |Cite
|
Sign up to set email alerts
|

Limited role of interim PET/CT in patients with diffuse large B-cell lymphoma treated with R-CHOP

Abstract: Positron emission tomography (PET) has been found useful in monitoring response to treatment of malignant lymphoma. We investigated the ability of interim PET to monitor response to standard dose R-CHOP chemotherapy in chemotherapy-naïve patients with diffuse large B-cell lymphoma (DLBCL). Between March 2004 and April 2009, 155 DLBCL patients treated with R-CHOP and available for interim and post-treatment PET/CT were identified and included in this analysis. Response, progression-free survival (PFS), and over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 18 publications
4
45
0
1
Order By: Relevance
“…(63%) achieved remission after a positive I-PET (24). These smaller studies provide reassurance that our findings are not a unique phenomenon.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…(63%) achieved remission after a positive I-PET (24). These smaller studies provide reassurance that our findings are not a unique phenomenon.…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, 2-y EFS and OS, stratified by I-PET response after 2-3 cycles chemotherapy, were comparable to recent studies from high-income countries, likewise using visual PET reporting and early I-PET scanning after 2-3 cycles (Table 3) (22)(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 63%
“…In DLBCL, early indication of poor response is especially important because salvage treatment of progressive or relapsed disease is less effective in the rituximab era. 134 However, although early data favored iPET, 55,57,59 more recent data have suggested iPET is less predictive for response with immunochemotherapy 30-32,58, 135,136 (Appendix Table A2, online only), and end-of-treatment PET is a better predictor.…”
Section: Role Of Ipetmentioning
confidence: 99%
“…28-32,93, [135][136][137] The drop in PPV may be related to improved outcomes with rituximab or better supportive care 126,138 or may possibly occur because so-called false-positive metabolic activity is more frequent with immunotherapy. 30 A different cutoff or combination of factors may be required for modern management of DLBCL.…”
Section: Role Of Ipetmentioning
confidence: 99%
“…These studies showed that patients with significant residual 18 F-FDG uptake after 2-3 cycles of chemotherapy had 2-y PFS rates of only 0%-30%. However, the widespread use of rituximab in NHL patients is associated with false-positive 18 F-FDG PET findings (13,26), suggesting a need for validation of the utility of interim 18 F-FDG PET response analysis in the rituximab era. Recently, 2 studies on interim 18 F-FDG PET in DLBL patients treated with rituximab-containing regimens were published (12,27).…”
Section: Discussionmentioning
confidence: 99%